Neutrophil infiltration to the brain is platelet‐dependent, and is reversed by blockade of platelet GPIbα. Issue 2 (8th February 2018) - Giles, James A.; Greenhalgh, Andrew D.; Denes, Adam; Nieswandt, Bernhard; Coutts, Graham; McColl, Barry W.; Allan, Stuart M.
Summary: Neutrophils are key components of the innate immune response, providing host defence against infection and being recruited to non‐microbial injury sites. Platelets act as a trigger for neutrophil extravasation to inflammatory sites but mechanisms and tissue‐specific aspects of these interactions are currently unclear. Here, we use bacterial endotoxin in mice to trigger an innate inflammatory response in different tissues and measure neutrophil invasion with or without platelet reduction. We show that platelets are essential for neutrophil infiltration to the brain, peritoneum and skin. Neutrophil numbers do not rise above basal levels in the peritoneum and skin and are decreased ( 60%) in the brain when platelet numbers are reduced. In contrast neutrophil infiltration in the lung is unaffected by platelet reduction, up‐regulation of CXCL‐1 (2·4‐fold) and CCL5 (1·4‐fold) acting as a compensatory mechanism in platelet‐reduced mice during lung inflammation. In brain inflammation targeting platelet receptor GPIb α results in a significant decrease (44%) in platelet‐mediated neutrophil invasion, while maintaining platelet numbers in the circulation. These results suggest that therapeutic blockade of platelet GPIb α could limit the harmful effects of excessive inflammation while minimizing haemorrhagic complications of platelet reduction in the brain. The data also demonstrate the ability to target damaging brain inflammation in stroke and related disorders without compromising lung immunity and hence risk of pneumonia, a major complication post stroke. In summary, our data reveal an important role for platelets in neutrophil infiltration to various tissues, including the brain, and so implicate platelets as a key, targetable component of cerebrovascular inflammatory disease or injury. Abstract : In this manuscript we present novel data that platelets are not only necessary for tethering and rolling of neutrophils but also that neutrophil infiltration to inflamed tissue beds can be blocked, in specific tissues, by a reduction in platelets. Therefore, the work reveals tissue‐specific innate immune responses that we believe are an important concept in immunology. We also show that platelet‐mediated neutrophil invasion to the brain is dependent upon the platelet receptor GPIbα, therefore providing a potential therapeutic intervention strategy for neutrophil‐mediated diseases/injury to the brain.